Global environmental, social and governance policy : towards a universal model - Biswas, Prana Krishna; Dygas, Robert (Routledge studies in the economics of business and industry, 2026)
This book sheds light on environmental, social and governance (ESG) policy principles, practice and the implications of integrating ESG factors into business operations, investment strategies and corporate governance frameworks, across both developed and developing countries (Europe, Asia and the US). This is the first book which brings together academics from different continents to share their views and knowledge on this subject, with a focus on regional perspectives. The book argues that exhaustive research has been conducted on ESG integration for financial performance, risk management and stakeholder engagement in developed countries, with research showing a positive correlation between ESG performance and value creation. Furthermore, transparency and accountability in ESG disclosures by companies have played a critical role in the firm's performance and market value. This is also supported by the regulatory initiatives taken by the government in promoting industry standards for ESG practices. On the contrary, developing countries face several challenges in the adoption and implementation of sustainable practices. The book underscores the importance of maintaining a harmonious balance between economic development and environmental and societal factors. The book examines the norms and standards that constitute ESG in Asia, Europe and the US, analyses whether ESG supports business management and GDP growth, and looks at the main barriers to implementing ESG Policy by companies in the selected regions. It includes a comprehensive set of case studies from each region and across various sectors to demonstrate how ESG policy is implemented around the world. Researchers, scholars and students who specialize in sustainable development, development economics and international business management will be interested in this book.